Mechanical property evaluation of carbon nanotubes reinforced plasma sprayed YSZ-alumina composite coating. Issue 6 (15th April 2018) - Thakare, J.G.; Pandey, Chandan; Mulik, R.S.; Mahapatra, M.M.
Abstract: Yttria (8%) stabilized zirconia (8YSZ)-alumina-carbon nanotube (CNT) composite coatings were deposited using air plasma spray (APS) technique. Three zirconia alumina (ZA) composite coatings, without CNT reinforcement, and with 1%CNT, 3%CNT reinforcement were deposited using identical process parameters (500 A and 66 V). Indentation method was used to characterize mechanical behavior of coatings. The CNT reinforced composite coating showed superior mechanical properties as compared to the conventional 8YSZ coating. The addition of alumina and 1%CNTs increased the Young's modulus by around 25% and 40%, respectively. However, the increase in CNT content decreased the Young's modulus as a result of CNT agglomeration. The hardness, fracture toughness increased with addition of alumina and CNT. The fracture toughness increased from 0.55 ± 0.26 MPa m 1/2 for 8YSZ to 1.76 ± 0.65 MPa m 1/2 for 17%alumina-3%CNT reinforcement due to various toughening mechanisms like crack deflection, bridging etc. The maximum displacement of indenter was found to decrease from 176 nm for conventional YSZ coating to 120 nm for 3% CNT reinforced coating. The surface roughness (Ra) was found to be decrease with alumina addition and CNT reinforced coating. The CNT reinforced coating showed surface roughness of around 6 µm. Scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS) was used to characterize the coating microstructure and elemental composition respectively.